2011
DOI: 10.1111/j.1365-2842.2011.02211.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of various jaw motor tasks on body sway

Abstract: Alterations of body sway caused by isometric contractions of the jaw muscles have been reported previously. The objective of this study was to test if motor tasks of the masticatory system with different control demands affect body posture differently during quiet stance. Position and sway displacements of the center of foot pressure (COP) were measured for 20 healthy subjects who either kept the mandible at rest or performed unilateral and bilateral maximum voluntary teeth clenching, feedback-controlled bitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
56
2
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 38 publications
8
56
2
2
Order By: Relevance
“…(Fransson et al, 2000(Fransson et al, , 2003Rogers et al, 2001;Massion, 1994). There is evidence that the sensory-motor system of the jaw can influence the vestibular (Park et al, 2014), neck (Davies, 1979;Ehrlich et al, 1999) and ocular systems and can therefore also affect the postural control system (Hellmann et al, 2011). Our results, showing significant decreases in COG velocity between different jaw positions, seem to support this and show that activation of the jaw sensory-motor system can affect postural control mechanisms.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…(Fransson et al, 2000(Fransson et al, , 2003Rogers et al, 2001;Massion, 1994). There is evidence that the sensory-motor system of the jaw can influence the vestibular (Park et al, 2014), neck (Davies, 1979;Ehrlich et al, 1999) and ocular systems and can therefore also affect the postural control system (Hellmann et al, 2011). Our results, showing significant decreases in COG velocity between different jaw positions, seem to support this and show that activation of the jaw sensory-motor system can affect postural control mechanisms.…”
Section: Discussionsupporting
confidence: 80%
“…Impaired balance control, either due to aging or to some disease, has been identified as one of the most influential risk factors for falling (Lipsitz and Goldberger, 1992;Goldberger et al, 2002;Close et al, 2005;Stevens et al, 2006;Moreland et al, 2003). Patients with a high risk of falling are characterized by increased variability of postural motion (Morrison et al 2010), body sway with less overall motion, and increased COG velocity (Hellmann et al 2011). Consideration of our results may be helpful in the clinical management of patients at higher risk of falling in order to increase their postural stability.…”
Section: Clenched Jaw Eyes Openmentioning
confidence: 99%
See 1 more Smart Citation
“…One limitation of the abovementioned studies [1][2][3], however, is the lack of active controls, as used by Miyahara et al [5]. The authors reported that soleus H reflex was not only increased by voluntary clenching of the teeth, but also by isometric contraction of the wrist extensors or by clenching of the fists.…”
Section: Introductionmentioning
confidence: 94%
“…Recently, submaximum clenching of the jaw was reported to significantly improve postural stability and to decrease the sway of cranial body segments in upright unperturbed stance [1][2][3]. The authors concluded that these improvements were induced by modulation of somatosensory input, particularly of the neck muscles [4], and facilitation of ankle extensor and flexor muscles [5,6], concomitant with attenuated reciprocal Ia inhibition [6].…”
Section: Introductionmentioning
confidence: 94%